Asthma-COPD overlap: A Portuguese survey - Padrão, E. (2018)
Introduction: The overlap between asthma and chronic obstructive pulmonary disease (COPD) (ACO) has been discussed for many years but clinical recommendations for this entity have been diverse. This study is intended to reach a consensus on diagnosis, treatment and patient orientation for ACO, within the Portuguese medical community. Methods: This study was conducted by a multidisciplinary panel of experts from three distinct medical specialties (Pulmonology, Family Medicine and Immunoallergology). This panel selected a total of 190 clinicians, based on their expertise in obstructive airway diseases, to participate in a Delphi structured survey with three rounds of questionnaires. These results were ultimately discussed, in a meeting with the panel of experts and some of the study participants, and consensus was reached in terms of classification criteria, treatment and orientation of ACO patients. Results: The majority of clinicians (87.2%) considered relevant the definition of an overlap entity between asthma and COPD. A consensus was achieved on the diagnosis of ACO – presence of simultaneous clinical characteristics of asthma and COPD together with a fixed airflow obstruction (FEV1/FVC < 0.7) associated with 2 major criteria (previous history of asthma; presence of a previous history of smoking exposure and/or exposure to biomass combustion; positive bronchodilation test (increase in FEV1 of at least 200 mL and 12%) on more than 1 occasion) plus 1 minor criteria (history of atopy; age ≥40 years; peripheral eosinophilia (>300 eosinophils/μL or >5% of leukocytes); elevation of specific IgEs or positive skin tests for common allergens). A combination of inhaled corticosteroid (ICS) with long-acting beta2-agonist (LABA) or long-acting muscarinic antagonist (LAMA) was considered as first line pharmacological treatment. Triple therapy with ICS plus LABA and LAMA should be used in more severe or symptomatic cases. Non-pharmacological treatment, similar to what is recommended for asthma and COPD, was also considered highly important. A hospital referral of ACO patients should be made in symptomatic or severe cases or when there is a lack of diagnostic resources. Conclusions: This study highlights the relevance of defining ACO, within the Portuguese medical community, and establishes diagnostic criteria that are important for future interventional studies. Recommendations on treatment and patient's orientation were also achieved.